Environmental hygiene and healthcare-associated infection: a time-series study based on generalized additive model - Li, Renhua; Wang, Zhongjie; Huang, Mingqi; Liao, Daiying; Yuan, Zhe; Qian, Keli (Frontiers in Public Health, 2025)
ObjectiveTo quantitatively analyze the impact of environmental hygiene on the occurrence of healthcare-associated infection (HAI).MethodsMonitoring data of HAI and environmental hygiene from a tertiary first-class hospital from July 1, 2022, to December 31, 2024, were collected, and the impact of environmental bacterial colony forming unit (CFU) on the occurrence of HAI was analyzed by a time-series generalized additive model (GAM).ResultsThe single-contamination model showed a significant positive correlation between HAI and total colony count, high-touch surface (HTS) colony count, and staff' hands colony count. The same pattern was observed in the multi-contamination model.ConclusionThere is a significant correlation between environmental hygiene and the occurrence of HAI.